Shurah Al-Hub fii Qashidah Hub Bila Hudud lii Nizar Qabbani: Dirasah Tahliliyah Simiyaiyah - Firdaus, Muhammad; Ulfa, Fitria (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study aims to find a semiotic description of love contained in Nizar Qabbani's poem entitled